PELAKSANAAN EKSTENSIFIKASI DAN INTENSIFIKASI PAJAK DALAM RANGKA PENINGKATAN PENERIMAAN PAJAK PADA KPP PRATAMA KALIDERES - SEPTIANY, CHELSEA; WIJAYA, WILLIEM CHAHYA (E-Jurnal Akuntansi TSM, 2021)
The purpose of this study is to know the procedures of the implementation of tax extensification and intensification. This study also aims to know the suitability of the implementation of tax extensification and intensification, to know the effectiveness of tax extensification and intensification and to find out the contribution of tax extensification activities and intensification to tax revenue at Tax Office (KPP) Pratama Kalideres. The research method used in this research is comparative descriptive. In this method the authors explain the subject and object research based on facts, and compare the suitability between the data obtained from the research object consisting of the advice letter that issued with the applicable regulations, and tax revenue 2014-2016 at KPP Pratama Kalideres. Based on the results of data analysis procedures and procedures for implementation and the drafting or formulation of advices letter for the implementation of extensification and tax intensification in KPP Pratama Kalideres has been in accordance with the regulations of Directorate General of Tax No. PER-35 / PJ / 2013. The effectivity of extensification and counseling section 2014-2016 is ineffective due to decreased every year, at the same time the effectivity of supervision and consultation section II, III and IV in 2014-2016 is less effective. The contribution of the implementation of tax extensification and intensification with the advises letter to the tax revenue in 2014-2016 is very less